Hemodynamic and Conduction System Outcomes in Sievers Type 0 and Sievers Type 1 Bicuspid Aortic Valves Post Transcatheter Aortic Valve Replacement. Issue 3 (4th May 2021) - Kumar, Kris; Simpson, Timothy F.; Akhavein, Reyhaneh; Rajotte, Katherine; Weller, Segolene; Fuss, Cristina; Song, Howard K.; Golwala, Harsh; Zahr, Firas; Chadderdon, Scott M.
ABSTRACT: Background : A retrospective analysis of severe bicuspid aortic stenosis was performed to evaluate hemodynamic profiles and incidence of adverse conduction effects in Sievers Type 0 compared to Sievers Type 1 morphologies after transcatheter aortic valve replacement (TAVR) with a self-expanding prosthesis. In the past decade there has been a transition to treating lower risk patients with TAVR. While overall outcomes in patients with bicuspid aortic valves (BAV) have improved, hemodynamic and conduction system challenges still exist. Methods : Moderate- to high-risk patients with BAV who underwent TAVR with a self-expanding prosthesis from 01/01/2017 to 09/01/2019 were reviewed. Transthoracic echocardiographic (TTE) and electrocardiogram (ECG) data were analyzed at baseline and at 30-day follow-up. Computed tomography (CT) of the aortic annulus was analyzed in all patients pre-TAVR and in a subset of 10 patients post-TAVR. Results : The cohort consisted of 10 Sievers Type 0 and 20 Sievers Type 1 patients, mean age 68 y, and Society of Thoracic Surgeons (STS) risk 4.6 ± 3.7%. Post-TAVR, Sievers Type 1 BAV had a superior hemodynamic profile, with lower gradients and less paravalvular leak compared to Type 0. Post-TAVR valve eccentricity was unchanged in Type 1 but markedly altered in Type 0 BAV. Conversely, Type 1 BAV demonstrated an increased incidence of new left bundle branch block (LBBB). Conclusions : Sievers Type 1 anatomy was associated with a superior hemodynamic profile but an increased incidence of LBBB when compared to Sievers Type 0 post-TAVR. As TAVR shifts to a lower risk cohort, understanding how BAV morphologies affect long-term hemodynamics and conduction abnormalities warrants continued study. Abbreviations : AS: aortic stenosis; AV: aortic valve; AVA: aortic valve area; BAV: bicuspid aortic valve; CT: computed tomography; CTA: computed tomography angiography; DVI: dimensionless index; ECG: electrocardiogram; EI: eccentricity index LBBB: left bundle branch block; LVEF: left ventricular ejection fraction; LVOT: left ventricular outflow tract; NYHA: New York Heart Association Classification; PVL: paravalvular leak; PPM: permanent pacemaker; SAVR: surgical aortic valve replacement; STS: Society of Thoracic Surgeons; SV: stroke volume; TAVR: transcatheter aortic valve replacement; TTE: transthoracic echocardiogram; VARC-2: Valve Academic Research Consortium 2.